Effectiveness of preimplantation genetic testing for aneuploidy in improving clinical and neonatal outcomes for patients with recurrent pregnancy loss - Li, Jieliang; Li, Zhiming; Lin, Xiaoli; Ou, Zhanhui; Huo, Junye; Fang, Xiaowu; Du, Jing; Lin, Xiufeng; Wen, Xiaojun (Frontiers in Endocrinology, 2025)
ObjectivesThis study aimed to evaluate a clinical utility of preimplantation genetic testing for aneuploidy (PGT-A) in patients with recurrent pregnancy loss (RPL) and explore a population that benefits from it.MethodsWe analyzed 818 oocyte retrieval cycles and 1,165 frozen embryo transfer cycles from 797 patients with RPL. Stratified analyses were conducted based on age, number of miscarriages, chromosomal polymorphisms and ovarian reserve to compare clinical and perinatal outcomes between PGT-A and non-PGT-A groups.ResultsEuploid, aneuploid, and mosaic blastocysts accounted for 54.07%, 33.33%, and 12.60%, respectively. Age stratification analysis showed that PGT-A significantly improved the clinical pregnancy rate (CPR) and live birth rate (LBR) in patients under 38 years (CPR: 63.64% vs. 55.03%, P = 0.004; LBR: 53.03% vs. 43.25%, P = 0.002). In age group of 38 years or older, PGT-A was associated with a higher CPR (50.63% vs. 35.42%, P = 0.034), while the increase in LBR did not reach statistical significance (36.70% vs. 23.96%, P = 0.084). In patients with three previous miscarriages, PGT-A significantly improved CPR (74.70% vs. 42.13%) and LBR (55.42% vs. 32.02%) (P < 0.05). Chromosomal polymorphism analysis revealed that outcomes with PGT-A were superior for patients with normal karyotypes, whereas no significant differences were observed among those with polymorphisms. PGT-A significantly improved CPR (59.68% vs. 52.37%, P = 0.004) and LBR (49.41% vs. 40.56%, P < 0.01) in patients with normal ovarian reserve. Although CPR increased in those with a diminished ovarian reserve (62.50% vs. 39.45%, P = 0.015), this was accompanied by a marked increase in the miscarriage rate (40.00% vs. 23.36%, P = 0.029). Consequently, no statistical difference was noted in LBR.ConclusionsPGT-A can significantly improve CPR and LBR in patients with RPL aged < 38 years with a history of three miscarriages, a normal chromosomal karyotype, and a normal ovarian reserve. For patients with a history of two miscarriages, PGT-A notably enhances a success of clinical pregnancy conversion into live birth. However, for individuals with diminished ovarian reserve, chromosomal polymorphisms, or a history of four or more miscarriages, a cautious and individualized assessment is necessary.